2007
DOI: 10.1016/j.jaci.2006.11.508
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus NL63 Illnesses in Infancy are a Risk Factor for Asthma at Age Six

Abstract: RATIONALE: In infancy, rhinovirus illnesses and severe RSV bronchiolitis indicate increased risk for recurrent wheezing and asthma, but there is less information about other viruses. We evaluated the frequency and severity of metapneumovirus (HMPV) and coronavirus (HCV) infections in a high-risk group of infants. METHODS: Nasal lavage samples were obtained in the first year of life during scheduled study visits and symptomatic respiratory illnesses as part of the Childhood Origins of Asthma Project (COAST). Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2010
2010
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
2
1
Order By: Relevance
“…The results of the COAST Study 7,8,12 and the subsequent study from Australia 9 appear to be in contrast to our initial findings that the administration of palivizumab in infancy protects premature subjects against subsequent recurrent wheezing in the first 3 to 4 years of life. 6 This prompted us to examine the potential for a differential effect of RSV prevention in those with and without an atopic diathesis.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…The results of the COAST Study 7,8,12 and the subsequent study from Australia 9 appear to be in contrast to our initial findings that the administration of palivizumab in infancy protects premature subjects against subsequent recurrent wheezing in the first 3 to 4 years of life. 6 This prompted us to examine the potential for a differential effect of RSV prevention in those with and without an atopic diathesis.…”
Section: Discussioncontrasting
confidence: 97%
“…A Spanish study showed that human metapneumovirus and RSV in infancy were associated with asthma at age 5 years, 11 and the COAST Study showed that human coronavirus NL63 but not human metapneumovirus produced asthma at age 6 years. 12 Thus, the relationship between early RSV LRTI and allergic sensitization in the development of asthma at a later age is still unresolved. This controversy prompted us to examine the effect of the family history of atopy on the prevention of later recurrent wheezing in premature infants who had received palivizumab in the first year of life compared to controls.…”
mentioning
confidence: 99%
“…There have been studies suggesting that other viruses may be important in the development of subsequent wheezing/asthma in infants born at term. In the COAST study, rhinovirus was the most important association of development of wheezing at 3 [14] and 6 [10] years in children with a strong family history of atopy, and in another study [18], human coronavirus NL63 was associated with asthma at 6 years. Other studies have suggested that other viruses in combination with RSV may increase subsequent morbidity.…”
Section: Discussionmentioning
confidence: 93%